Social Responsibility Accounting And Profitability Of Dangote Cement PLC Listed in the NSE - Etale, Lyndon M.; Sawyerr, Ayaundu E. (Advances in Social Sciences Research Journal, 2020)
This study examined the relationship between social responsibility accounting and profitability using Dangote Cement PLC (DCP) as a case study. The study adopted staff training and development, staff welfare and healthcare cost, and staff pension and gratuity as proxy for social responsibility accounting (the explanatory variables), while profit after tax representing profitability was adopted as the response variable. Secondary data was collected from the annual financial statements of DCP for the period 2010 to 2018. The study employed descriptive statistics and multiple regression analysis based on the E-view 10 software for data analysis. The results revealed that staff training and development, and staff welfare and healthcare cost had significant positive relationship with profit after tax, while staff pension and gratuity had an insignificant negative link with profit after tax. The coefficient of determination (R-squared) value of 0.99 indicated that 99% of changes in the response variable are accounted for by the combined effect of changes in the explanatory variables; and results are statistically significant with a probability of F-statistic value of 0.000000 (at 5% level of significance). Also, the adjusted R- squared value of 0.99 indicated that the model used for the analysis is a proper and good fit. The study concluded that social responsibility accounting is significantly related to profitability. Based on the findings of this study it is recommended that the management of DCP should continue with the social responsibility accounting practices for its good social image as this would guarantee the long run sustainable growth of the company.